Study of the internal structureof thin polymer skins with alpha-spectrometric method - Әбілдaев Ә.Х.; Смaдиевa П.А.; Шинбулaтов С.К. (Recent Contributions to Physics, 2018)
In the article given scientific information on the preparation of polymer technology, the analysis of traditional methods to study theiri nternal structure, and then referred to later appears alpha-spectrometric method. Using these methods, we studied the internal structure of polyethylene membranes prepared by two techniques (in low pressure, high pressure). Display in gwinning and weaknesses of each method-polarizing microscope, X-ray diffraction and electron micros copy techniques to study the internal structure of thin polymer skins is logical to give them up. The article gives the experimental results obtained on a polarizing microscope and alpha spectrometer. The results are compared with other results. As a result, the decision to continue the investigation.